2006
DOI: 10.1017/s0022029905001548
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cellular and whey components in buffalo milk

Abstract: High somatic cell count (SCC) affects milk quality and cheesemaking, resulting in a reduction in cheese yield and quality. In dairy cows, quarter milk samples with > 200,000 cells/ml are considered to have subclinical mastitis, while there is much uncertainty on the corresponding levels of SCC in buffalo milk. In this study 30 lactating water buffaloes were selected and SCC, differential somatic cell counts and several whey components were tested in quarter milk samples to assess the relationship between infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
10
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 7 publications
8
10
0
2
Order By: Relevance
“…Our study indicated a high and significant (p<0.01) correlation (0.741) between SCC and lactoferrin. Various workers were in conformity with the above results (Piccinini et al 2006;Cheng et al 2008;Al-Majali et al 2007). Lactoferrin content was elevated in mastitis and there was a close relationship between SCC and Lactoferrin content (Chen et al 2004).…”
Section: Snp Identificationsupporting
confidence: 72%
“…Our study indicated a high and significant (p<0.01) correlation (0.741) between SCC and lactoferrin. Various workers were in conformity with the above results (Piccinini et al 2006;Cheng et al 2008;Al-Majali et al 2007). Lactoferrin content was elevated in mastitis and there was a close relationship between SCC and Lactoferrin content (Chen et al 2004).…”
Section: Snp Identificationsupporting
confidence: 72%
“…All SCCs of the farm milk samples were below the EU legislation threshold (400 × 10 3 cells/mL), also suggesting that cow management on these farms was appropriate (Smith, 2002;Piccinini et al, 2006). The marginal difference in SCC between 96 h (89,000 cells/mL) and 0 h (98,000 cells/mL) is probably not relevant, and levels remained below the EU threshold during storage.…”
Section: Sccmentioning
confidence: 94%
“…Quando se considerou a média de CCS (400.000 cel/mL) estabelecida por Piccinini et al (2006) como ponto de corte para o leite de búfala, observou-se que 220 (54,9%) amostras negativas e 181 (45,1%) positivas ao exame microbiológico apresentaram média de CCS ≤400.000 cel/mL, respectivamente. Quando a média de CCS foi >400.000 cel/mL, observouse que 146 (60,8%) amostras foram positivas e 94 (39,2%) negativas no exame microbiológico.…”
Section: Resultsunclassified
“…Piccinini et al (2006) sugeriram a contagem de 400.000 células/mL como ponto de triagem para o leite bubalino. Entretanto, diversos autores adotaram o valor de 500.000 células/mL para selecionar os quartos com presença ou ausência do quadro subclínico, sem necessariamente utilizarem a confirmação microbiológica (Vianni et al 1990, Tuteja et al 2001, Singh et al 2002, Vivek et al 2002, Dhakal 2004, Singh et al 2004.…”
Section: Introductionunclassified